Pengaruh Digital Marketing, Media Sosial, dan Penggunaan QRIS terhadap Kenaikan Omzet UMKM: Studi Kasus UMKM di Kecamatan Boyolali - Alexandra Ratu Maharani Bere; Susilaningtyas Budiana Kurniawati; Supartini Supartini (Economic Reviews Journal, 2026)
This study examines the effect of digital marketing, social media, and the use of QRIS on the increase in MSME turnover in Boyolali District. MSMEs play a strategic role in the Indonesian economy, yet many still face limitations in marketing reach and transaction efficiency. This research uses a quantitative approach with a survey method. The population consists of 455 MSMEs, with samples selected using purposive sampling. Data were analyzed using multiple linear regression. The results show that digital marketing, social media, and QRIS each have a positive and significant effect on increasing MSME turnover. Simultaneously, these three variables significantly influence turnover growth. The findings indicate that integrated digital strategies and digital payment adoption are important drivers of MSME performance improvement.